AFFECTIVE HEALTH AND THE TEACHING OF PHYSICS, APPROACH TO A STUDY PROBLEM (Revista Contexto & Educação, 2022)
Currently, there are concerns about teaching and learning science and physics specifically. Given the above, a correct didactic application and recognition of the affective and emotional component are necessary and important, as elements of health in the science classroom. Likewise, from the point of view of health, emotions and affections affect the training process. This relationship in the classroom arises because the affective component is related to academic understanding, especially in matters of scientific knowledge, in which positive and/or negative valences in teachers and students affect the levels and behaviors of science learning. Therefore, at the Universidade Surcolombiana, specifically in the Bachelor of Natural Sciences and Environmental Education, whose objective is the initial training of teachers, the affective-emotional dimension of Health Education is resumed, evaluating its influence on the teaching and learning processes of science. Therefore, a documental analysis was carried out to recognize the discursive categories of 25 academic productions around science teaching and affective teaching. Thus, Educational Analytical Summaries were constructed for each revised text, under a qualitative approach. Therefore, the recognition of four categories stands out, which address the affective dimension (emotions) with the practice of teachers, the training of teachers and students. On the other hand, a category is registered where and include proposals in affective teaching in science teaching. Therefore, it can be established that most studies take into account the implications of the affective dimension in the process of learning physics. In these references, elements such as commitment, interest, motivation and participation of students in their learning activities stand out. However, there are few studies that compile the experiences of teacher education and how their affective-emotional health changes over time and the achievement of their professional development.
Keywords: Affective Health; Emotions; Health Education; Physics Teaching